Determinantes de retorno anormal positivo no longo prazo: IPOS no Brasil - Fernandes, Caciano Gianechini (Universidade do Vale do Rio dos Sinos, 2019)
This research sought to verify which factors would be determinant for IPOs that had positive abnormal returns above market in the long run performance. We considered 152 IPOs of Brazilian firms placed in the market between 2004 and 2014, separating them into independent samples of IPOs with either positive or negative abnormal returns. We used the one-year, two-year and three-year periods after the IPO as the return period, calculated using the Buy-and-Hold Abnormal Return (BHAR) methodology through which it was possible to classify each IPO according to its return. In order to give greater solidity to the results, we analyzed the sample by means of Mann-Whitney and Kolmogorov-Smirnov nonparametric tests in cases of quantitative variables, and Pearson’s chi-squared and Fisher's Exact tests in cases of qualitative variables. The multivariate analysis consisted of the Ordinary Least Squares (OLS) method and the Probit and Logit methods, with the purpose of testing the probability of an abnormal positive return in light of the variables in the study. The found results indicate that IPOs of companies with above market positive abnormal return are negatively correlated with: 1) low interest rate levels (SELIC), 2) low levels of GDP, 3) years with a small number of IPO offers, 4) Market to Book (M/B) Ratio and 5) leverage. Otherwise positively correlated with: 1) Firms with presence of PE/VE, 2) Price/Earnings (P/E) Ratio, 3) IPOs with ItaúBBA as the underwriter, 4) the offering size and 5) country risk.
Keywords: IPO; Underpricing; Underperformance; Retorno anormal em IPOs; Hot Issue; Market Timming; IPO; Underpricing; Underperformance; Long Run Performance; Hot Issue; Market Timing; ACCNPQ::Ciências Sociais Aplicadas::Ciências Contábeis